Flood Mitigation Strategies for Settlement Area in Kediri District - Dinia Putri; Syafei, Arie Dipareza (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Referring to the IRB (Disaster Risk Index) released by BNPB in 2013, it shows that Kediri District is one of the administrative areas in East Java that has a high disaster index, one of which is flooding. Based on BPS data from Kediri Regency from 2012 to 2019 there was an increasing the population of 0.5-1%. In 2007-2019 the population increased by 8% accompanied by an increase in the number of residential areas by 25%. UU Number 24 of 2007 Article 47 states that to reduce disaster risk for people living in disaster-vulnerability areas, what must be done is to take mitigation actions. The results showed that areas with high flood vulnerability index were in the Badas, Kras, dan Ringinrejo. The evaluation results of the existing residential land in the three areas also stands on land that is not suitable for settlement and has low carrying capacity. So that five criterias are obtained along with alternative mitigation strategies that are suitable to be applied in Kediri District, especially in flood-vulnerability residential areas.